2015
DOI: 10.1177/183693911504000405
|View full text |Cite
|
Sign up to set email alerts
|

How Far have we come in respecting young Children in our research?: A Meta-Analysis of Reported early Childhood Research Practice from 2009 to 2012

Abstract: THIS PAPER SUMMARISES THE reporting of early childhood (EC) research practices through a meta-analysis of 10 scholarly international EC education journals. The analysis included 506 peer-reviewed primary research articles published between 2009 and 2012 (inclusive) involving young children between the ages of birth and eight years. These were reviewed for child status within research, researcher perspective of children involved in research and respectful research culture within EC research. This review provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
0
22
0
3
Order By: Relevance
“…In terms of relevance to other studies, while many researchers aspire to include children in meaningful ways – for example Hussain – a recent review of 506 peer‐reviewed studies conducted between 2009 and 2012 involving children aged 0–8 years analysed child positioning, researcher perspective and level of respectful culture in each study, concluding that only 3·4% positioned children in inclusive, participatory roles . Our study demonstrates that children can be included in research even from a relatively young age.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In terms of relevance to other studies, while many researchers aspire to include children in meaningful ways – for example Hussain – a recent review of 506 peer‐reviewed studies conducted between 2009 and 2012 involving children aged 0–8 years analysed child positioning, researcher perspective and level of respectful culture in each study, concluding that only 3·4% positioned children in inclusive, participatory roles . Our study demonstrates that children can be included in research even from a relatively young age.…”
Section: Discussionmentioning
confidence: 67%
“…Historically, children have been viewed as dependent and vulnerable objects of study, with primary informants typically being parents or clinicians . There are increasing calls for children to be actively involved in research studies, but evidence suggests children are frequently not engaged in meaningful ways . Health research is often undertaken on rather than with children, or their experiences are extrapolated or subsumed within adults’ views.…”
Section: Summary Of Other Elements Of the Clothing For The Relief Of mentioning
confidence: 99%
“…The qualitative design of our study satisfies the growing recent interest in qualitative research in children, 36 specifically in dermatology 37‐42 . FGs are particularly suited to children; indeed in their study of atopic dermatitis, Wake et al reported that children were eager to express their feelings and converse with doctors/psychologists and were able to talk about their experiences concisely, when given access to age‐appropriate means of communication 22‐26,37 .…”
Section: Discussionmentioning
confidence: 85%
“…The widespread idea that an RCT methodology is performed on rather than with children was now challenged. The experiences of simultaneously doing different kinds of data collections in the same project, made us agree on the risk of being objectified as educator or child applies to all forms of research practices (c. f. Mayne & Howitt, 2015). These bidirectional and creative discussions thus generated ethical protocols with specific guidelines on how to interact with the children at times of data collection, some of which will be discussed further below.…”
Section: The Problem Of Testingmentioning
confidence: 98%
“…In terms of ethics, more recently trained educational researchers, skilled in qualitative, action-and praxis-oriented research methodologies, generally view testing in RCT as something done to or on children (c.f. Mayne & Howitt, 2015). Testing is understood as subjectifying the child to a production of knowledge, by which the child becomes objectified.…”
Section: The Problem Of Testingmentioning
confidence: 99%